From guesswork to guidance: a delphi study on practices of talent identification and development in Para athletics - Carroll, A.; O`Riordan, A.; Pumpa, K. (Frontiers in Sports and Active Living, 2026)
Objectives: To determine best practices in Para athletics talent identification and development through a Delphi survey.